Strategic Management Support Systems - Fidler Christine; Rogerson Simon (Pitman Publishing, 1996)
An essential reading for anybody wanting to further their knowledge and skills in information systems planning, MSS, and in the effective combination of these two topics to derive strategic MSS. Preface, Acknowledgements, Introduction, Introduction and Overview, Management Support Systems, What is a Management Support System (MSS)? Technologies and MSS Opportunities, Information Handling Support with MSS, Passive Decision Making Support with MSS, Active Decision Making Support with MSS, MSS Development: Approaches and Techniques, Strategic Information Systems Planning (SISP), What is Strategic Information Systems Planning (SISP)?, SISP Methodologies and Techniques and Tools, How to Perform a SISP Exercise, Business Process Re-engineering, SISP Summary, Strategic MSS, Combining SISP/SCH and MSS: Strategic MSS, Conclusion, Index.